Producing Reflective Practice Capability: a Textual Analysis of Practice learning and Assessment Portfolios - Volante, Margaret A. (International Journal of Practice-based Learning in Health and Social Care, 2016)
Within portfolios used by nurse education programmes of higher education for practice learning and assessment, reflective narrative accounts are considered evidence of practice learning outcomes. Evaluation research of portfolios used in nurse education programmes is for the most part based on student perceptions, which show that students are conflicted on the inclusion of reflective accounts in the portfolio. This paper examines how structural influences of the practice learning milieu shape the reflective practice capability of the learner based on an analysis of 15 reflective narrative accounts from five practice learning and assessment portfolios of an undergraduate professional development programme for specialist community nursing in the United Kingdom. Ethnomethodology provided an orientation for single case textual analysis of related interactional sequences. Findings from a case comparison take the form of a local practice learning scene showing two structural patterns of orientation: a learning practice and the formal programme. These orientations can be differentiated by the accomplishment of reflective thinking-for-action, reflective thinking-for-evaluation and reflective thinking-for-critical enquiry. Reflective practice capability as an accomplishment of how the local practice learning milieu constitutes the portfolio approach to practice learning and assessment is presented through a case comparison of some interactions, roles and outcomes. The analysis draws attention to theoretical sensitivity to client outcomes for enhancing the portfolio as an enquiry-based approach for the accomplishment of reflective practice capability and the need for further investigation into the role of the academic nurse tutor in the portfolio approach.